Peningkatan Hasil Belajar Ekonomi Pada Kompetensi Dasar Menganalisis APBN Dan APBD Dalam Pembangunan Ekonomi Melalui Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) - Juheraeni (Shofanah Media Berkah, 2023)
This research aims to determine the improvement in learning outcomes in the Economics subject in class This research is classroom action research. The data collection techniques used in this research used observation and tests. The steps taken in this research are starting with observation to determine students' initial abilities in APBN and APBD material, then implementing a Think Pair Share (TPS) type cooperative learning model with a continuous learning cycle, and ending with a posttest at the end of each lesson. The results of the research show that implementing learning using the Think Pair Share (TPS) type cooperative learning model can improve student learning outcomes in economic subjects on APBN and APBD material in class XI Economics at SMA Negeri 8 North Penajam Paser who take APBN and APBD subjects. where from the results of these observations there was development both in terms of attendance and activeness and from the test results of students there was an increase where the results of the first cycle test showed the class average score reached 71.30 percent where 55.89 percent of students completed those who had not yet completed were 44.11 percent, while the implementation of cycle II showed an average class score of 80.29 percent, of which 88.24 percent of students had completed and 11.76 percent of students had not completed. This shows an increase.